Economies of Scale in China’s Civil Aviation Transportation Industry - Chongyi Jing, Mengyao Wu, Rubo Song, Yan Lu (Forest Chemicals Review)
To distinguish between economies of scale and economies of density, operational variables are introduced into the traditional translog cost function model. Financial and operational data of listed airlines in China (2005-2019) are used to measure factor cost elasticity, economies of scale, and their influencing factors in the air transportation industry. This research’s findings show that economies of scale and density values of China’s air transportation industry are 1.2728 and 1.2280, respectively. The economies of scale values of state-owned airlines and private airlines are 1.2994and 1.2374, respectively, and the economies of density values are 1.2386 and 1.2139, respectively. The former is better than the latter, because state-owned airlines have natural advantages in capital and personnel, and are more competitive for high-quality routes and time resources. The regression analysis shows that asset size does not have significant effects on economies of scale. The number of bases and the average size of aircraft types have a significant positive effect on economies of scale. Findings further reflect that an appropriate reduction of fleet commonality index is conducive to enhancing market adaptability. Thus, it reduces operating costs. The growth rate of economies of scale is faster than that of economies of density. This indicates that the impetus for the rapid development of China’s air transportation industry mainly comes from the rapid expansion of the size of the airline network.